Surface Tension of Liquids (Water, Chloroform and Acetone) by Capillary Rise Method - Adhikari, Dipak Raj; Budha, Tek Bahadur; Basnet, Anup; Adhikari, Shesh Kant; Baral, Shiva Pd. (BMC Journal of Scientific Research, 2023)
Surface tension is a crucial property of liquids that depends on the liquid’s composition. This study aims to compare the surface tension of water, chloroform, and acetone using the capillary rise method. It involves using a capillary tube with a known radius, dipping it vertically into a liquid, and measuring the height to which the liquid rises in the tube. The surface tension of the liquid can then be measured experimentally. This relates to height of the liquid in the tube, the radius of the tube, and the surface tension of the liquid. The height of the liquid in the tube is dependent on the radius of the tube, with a smaller radius resulting in a greater height. The surface tension of the liquid is inversely related to the radius of the capillary tube.